Pergeseran Fungsi Legislasi DPRD dalam Pembentukan Peraturan Daerah Untuk Memperkuat Kedudukan DPRD dalam Penyelenggaraan Pemerintahan Daerah - Dasril Radjab (Universitas Batanghari Jambi, 2018)
That with the presence of refomasi against the holding of the Government of the Republic of Indonesia, there was a significant change towards the function of legislation. If prior to the reformation by the UU No. 5 of the year 1974 the main legislation function is in the hands of the head Area, then after the Reformation was gradually shifted to the functions of DPRD, while the head of the Region carry out the Change was discussed along with Representatives The People Of The Region. Peregeseran the function of legislation to DPRD, then the seat of DPRD from both the political and juridical aspects become increasingly powerful as the element that organizes local governance. Disaran implementation of the function of legislation should run properly in the full sense of responsibility as well as follow all stages of the formation of local regulations that cover the stages of planning, drafting, discussion, enactment, assignment, and peyebarluasan